Pengaruh Supervisi dan Kepemimpinan Kepala Sekolah terhadap Kinerja Guru SD di Ilir Timur II: The Influence of Principal Supervision and Leadership on Elementary School Teacher Performance in Ilir Timur II - Putri Kusuma Wardani; Yasir Arafat; Syaiful Eddy (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2025)
This study aims to analyze the influence of supervision and principal leadership on the performance of elementary school teachers in Ilir Timur II District. The research employs a quantitative design, utilizing a survey method. The instrument, a questionnaire, has been tested for validity and reliability. The research population consists of all elementary school teachers in Ilir Timur II District, using a total sampling. Data are analyzed with multiple linear regression. The results indicate that supervision has a significant impact on teacher performance (? = 0.421; t = 4.32; p < 0.05). Principal leadership also significantly affects teacher performance (? = 0.367; t = 3.95; Sig. < 0.05). Together, supervision and principal leadership account for R² = 0.52, or 52%, of teacher performance. The remaining 48% is influenced by other factors. The novelty of this research lies in focusing on both supervision and principal leadership together in Ilir Timur II, a topic rarely studied integratively at the elementary level. This finding reinforces that a combination of systematic supervision strategies and effective leadership styles can be key to improving teacher performance in urban areas.